Temporal Changes in Fishing Yields, Trophic Dynamics, and Fisheries in Three Mediterranean Lagoons: Logarou and Rodia-Tsoukalio (Greece) and Mar Menor (Spain) - Theodore Zoulias; Angel Pérez-Ruzafa; Alexis Conides; Concepción Marcos; Sofia Reizopoulou; Dimitris Vafidis; Dimitris Klaoudatos (Ecologies, 2025)
This study analyzes 1980–2020 landings data from three Mediterranean coastal lagoons—the Logarou and Rodia-Tsoukalio Lagoons (NW Greece) and the Mar Menor Lagoon (SE Spain)—to assess ecosystem changes and fishing pressure dynamics. The findings classify these systems as low-yielding, with productivity ranked as follows: Yield Logarou > Yield Rodia-Tsoukalio = Yield Mar Menor. Mean trophic level analysis (mTrL) revealed significant differences driven by the contribution of detritivorous and mid-level carnivorous species (TrL Mar Menor > TrL Rodia-Tsoukalio > TrL Logarou). The fishing pressure indices suggest reduced fishing intensity in the Greek lagoons, while in Mar Menor, a stable Fisheries in Balance (FiB) trend corresponded with stable yields despite eutrophication. Cluster analysis (CA) and principal component analysis (PCA) linked ecosystem differences to sediment characteristics and changes in habitat structure. These results underscore a transition of Mediterranean coastal lagoons toward new ecological states, highlighting the urgent need for habitat conservation and adaptive management strategies to ensure sustainable fisheries under increasing environmental pressures. These findings may be extrapolated to similar transitional coastal ecosystems facing comparable anthropogenic stressors worldwide, providing a broader framework for understanding and managing lagoon systems under changing environmental conditions.